2016
DOI: 10.1177/1534735416651719
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Aerobic Physical Activity on Sleep Behavior in Breast Cancer Survivors

Abstract: Hypotheses. Sleep disorders are associated with an increased risk of cancer, including breast cancer (BC). Physical activity (PA) can produce beneficial effects on sleep. Study design. We designed a randomized controlled trial to test the effect of 3 months of physical activity on sleep and circadian rhythm activity level evaluated by actigraphy. Methods. 40 BC women, aged 35-70 years, were randomized into an intervention (IG) and a control group (CG). IG performed a 3 month of aerobic exercise. At baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 53 publications
1
52
0
Order By: Relevance
“…The inability of this meta-analysis to detect sleep quality benefits is not unexpected given that currently published randomized controlled trials (RCTs) of aerobic exercise (e.g., home-based walking, supervised aerobic exercise) in breast cancer survivors specifically have not consistently reported beneficial intervention effects on sleep (10,22,27,3032,34,37). In the seven trials measuring self-report, significant intervention effects were reported for overall sleep quality in four studies (two occurred during chemotherapy/radiation) (10,22,27,37), efficiency in one study (during chemotherapy) (10), latency in two studies (one during chemotherapy) (10,31), and sleep duration in one (post-chemotherapy/radiation) (30).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The inability of this meta-analysis to detect sleep quality benefits is not unexpected given that currently published randomized controlled trials (RCTs) of aerobic exercise (e.g., home-based walking, supervised aerobic exercise) in breast cancer survivors specifically have not consistently reported beneficial intervention effects on sleep (10,22,27,3032,34,37). In the seven trials measuring self-report, significant intervention effects were reported for overall sleep quality in four studies (two occurred during chemotherapy/radiation) (10,22,27,37), efficiency in one study (during chemotherapy) (10), latency in two studies (one during chemotherapy) (10,31), and sleep duration in one (post-chemotherapy/radiation) (30).…”
Section: Introductionmentioning
confidence: 94%
“…In the seven trials measuring self-report, significant intervention effects were reported for overall sleep quality in four studies (two occurred during chemotherapy/radiation) (10,22,27,37), efficiency in one study (during chemotherapy) (10), latency in two studies (one during chemotherapy) (10,31), and sleep duration in one (post-chemotherapy/radiation) (30). Another post chemotherapy/radiation trial reported beneficial effects on accelerometer measured efficiency, latency, and awake time (34). The three trials using both accelerometer and self-report measures did not occur during chemotherapy or radiation and reported no effect on accelerometer efficiency and latency even when global self-report sleep quality benefits were found (27,30,31).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In March 2014, 42 women volunteered to participate in the AEI trial (Roveda et al., ). The trial design follows the CONSORT 2010 guidelines (Schulz, Altman, & Moher, ) and it is summarised in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Women included in the IG attended a supervised AEI for 3 months (from April to June 2013) with an expert sport therapist (Roveda et al., ). In addition, women were also invited to do a moderate‐intensity exercise at home (walking or other aerobic activity) for at least 30 min every day as suggested by WCRF/AICR (World Cancer Research Fund & American Institute for Cancer Research ).…”
Section: Methodsmentioning
confidence: 99%